Dispensing antiretrovirals during Covid-19 lockdown: re-discovering community-based ART delivery models in Uganda - Henry, Zakumumpa; Christopher, Tumwine; Kiconco, Milliam; Spicer, Neil (BMC Health Services Research, 2022)
Background: The notion of health-system resilience has received little empirical attention in the current literature on the Covid-19 response. We set out to explore health-system resilience at the sub-national level in Uganda with regard to strategies for dispensing antiretrovirals during Covid-19 lockdown. Methods: We conducted a qualitative case-study of eight districts purposively selected from Eastern and Western Uganda. Between June and September 2020, we conducted qualitative interviews with district health team leaders (n = 9), ART clinic managers (n = 36), representatives of PEPFAR implementing organizations (n = 6).In addition, six focus group discussions were held with recipients of HIV care (48 participants). Qualitative data were analyzed using thematic approach. Results: Five broad strategies for distributing antiretrovirals during ‘lockdown’ emerged in our analysis: accelerating home-based delivery of antiretrovirals,; extending multi-month dispensing from three to six months for stable patients; leveraging the Community Drug Distribution Points (CDDPs) model for ART refill pick-ups at outreach sites in the community; increasing reliance on health information systems, including geospatial technologies, to support ART refill distribution in unmapped rural settings. District health teams reported leveraging Covid-19 outbreak response funding to deliver ART refills to homesteads in rural communities. Conclusion: While Covid-19 ‘lockdown’ restrictions undoubtedly impeded access to facility-based HIV services, they revived interest by providers and demand by patients for community-based ART delivery models in case-study districts in Uganda.